Produksi Bioetanol Dari Tepung Agar Gracilaria verrucosa (Hudson) Papenfuss yang Dihidrolisis Dengan Menggunakan Larutan Asam Sulfat - Saputra, Wahid Agung; Susanto, AB; Pramesti, Rini (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Fossil fuels are non-renewable fuels and overexploited. It has an impact on depletion oil reserves so needed renewable energy such as bio-ethanol. Bioethanol is alternative fuel made from biomass containing component sugars, starches, and cellulose. Agar is polysaccharide in cell wall seaweed Gracilaria verrucosa. Polysaccharides can be hydrolyzed with chemically or enzymatically into monosaccharides and then be fermented into bioethanol. The purpose of this study was to determine the potential of powder agar for bioethanol feedstock; optimum sulfuric acid to hydrolyze powder agar, and knowing optimum fermentation time on ethanol production. The study was conducted from February to June 2012 in Microbiology Laboratory, Research Center for Biology-LIPI, Cibinong. Powder agar is obtained from manufacturers in Malang. Yeast Saccharomyces cerevisiae is a collection of LIPI-MC. Reducing sugar content was analyzed by the method of Miller (1959), while concentration ethanol were analyzed by Gas Chromatography (GC). Method used in this study is an experimental laboratory for the hydrolysis and repeatable measurements for fermentation processes. Hydrolysis process using concentration H2SO4 of 0M, 0.1 M, 0.3 M, and 0.5 M. Fermentation using yeast S. cerevisiae with the incubation time 120 hours. Results showed powder agar can be used as raw material for bioethanol. Optimum reduction sugar 35.38 mg/ml Â± 0.59 obtained in H2SO4 0.3 M. Ethanol Optimum 0.77%, obtained at 120 hours incubation.